2010
DOI: 10.17305/bjbms.2010.2712
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ivs14+1G>A Polymorphism of Dpyd Gene in a Group of Bosnian Patients Treated with 5-Fluorouracil and Capecitabine

Abstract: Adverse drug reactions still pose an important clinical problem. Dihydropyrimidine dehydrogenase (DPD) is an enzyme that regulates 5-FU quantities available for anabolic processes and hence affects its pharmacokinetics, toxicity and efficacy. There are several studies describing a hereditary (pharmacogenetic) disorder in which individuals with absent or significantly reduced DPD activity may even develop a life-threatening toxicity following exposure to 5-FU. The most common mutation is known as the DPYD*2A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…For the literature control cohort, used for comparison of toxicity, a total of 17 published studies were selected, describing clinical data on 86 DPYD *2A variant allele carriers . Patient characteristics of the historical cohort are included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…For the literature control cohort, used for comparison of toxicity, a total of 17 published studies were selected, describing clinical data on 86 DPYD *2A variant allele carriers . Patient characteristics of the historical cohort are included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the enzyme deficiency state of the 5-FU degradation pathway causes damage and degeneration of the central nervous system (8, 14, 16). Thus DPYD is known as a biomarker of severe toxicity in chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic variations have been reported in previous studies. DPYD * 2A (rs3918290), located in the intron site, plays the role of an alternative splicing variant, and other polymorphisms such as DPYD * 9A ( rs1801265 ), DPYD * 7 (rs72549309), DPYD * 8 (rs1801266), DPYD * 9B (rs1801267), and DPYD * 10 (rs1801268), affect DPYD enzyme activity in other ways (8-14). …”
Section: Introductionmentioning
confidence: 99%
“…DPD-deficient patients exhibit a normal phenotype until administered with 5-FU or capecitabine. It has been estimated that nearly 3-5% of the general population has the DPD activity below normal (Cerić et al, 2010).…”
Section: Introductionmentioning
confidence: 99%